Cervicovaginal cytokines, sialidase activity and bacterial load in reproductive-aged women with intermediate vaginal flora - Santos-Greatti, Mariana Morena de Vieira [UNESP] (2016)
Studies have shown that not only bacterial vaginosis, but also intermediate vaginal flora has deleterious effects for women's reproductive health. However, literature still lacks information about microbiological and immunological aspects of intermediate flora. Objective: To characterize intermediate flora regarding levels of Interleukin (IL)–1beta, IL-6, IL-8, tumor necrosis factor-alpha, interleukin 1 receptor antagonist (IL-1ra), IL-10, sialidase; loads of Gardnerella vaginalis, total bacteria and to verify whether it is closer related to normal flora or bacterial vaginosis. This cross-sectional study enrolled 526 non-pregnant reproductive-aged women distributed in 3 groups according to pattern of vaginal flora using Nugent's system in normal, intermediate and bacterial vaginosis. Cervicovaginal levels of cytokines, sialidases, loads of G. vaginalis and total bacteria were assessed by ELISA, conversion of MUAN and quantitative real-time PCR, respectively. A principal component analysis(PCA) using all measured parameters was performed to compare the three different types of flora. Results showed that intermediate flora is associated with increased cervicovaginal IL-1beta in relation to normal flora(P < 0.0001). When compared to bacterial vaginosis, intermediate flora has higher IL-8 and IL-10 levels(P < 0.01). Sialidases were in significantly lower levels in normal and intermediate flora than bacterial vaginosis(P < 0.0001). Loads of G. vaginalis and total bacterial differed among all groups(P < 0.0001), being highest in bacterial vaginosis. PCA showed that normal and intermediate flora were closely scattered, while bacterial vaginosis were grouped separately. Conclusion: Although intermediate flora shows some differences in cytokines, sialidases and bacterial loads in relation to normal flora and bacterial vaginosis, when taken together, general microbiological and immunological pattern pattern of intermediate flora resembles the normal flora.